2020
DOI: 10.1136/svn-2020-000376
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular treatment of bilateral intracranial vertebral artery aneurysms: an algorithm based on a 10-year neurointerventional experience

Abstract: BackgroundThe management of bilateral intracranial vertebral artery dissecting aneurysms (IVADAs) is controversial, and requires the development of endovascular treatment modalities and principles. We aim to investigate the endovascular treatment strategy and outcomes of bilateral IVADAs.MethodsWe identified all bilateral IVADAs at a high-volume neurointerventional centre over a 10-year period (from January 2009 to December 2018). Radiographic and clinical data were recorded, and a treatment algorithm was deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…After title-abstract and full-text screenings (Figure 1: PRISMA flow diagram), 1095 patients from 56 studies 28,1058 underwent EVT for intracranial artery dissections were included in this analysis (Table 1). The publication timeline of included studies 1999 to 2021.…”
Section: Resultsmentioning
confidence: 99%
“…After title-abstract and full-text screenings (Figure 1: PRISMA flow diagram), 1095 patients from 56 studies 28,1058 underwent EVT for intracranial artery dissections were included in this analysis (Table 1). The publication timeline of included studies 1999 to 2021.…”
Section: Resultsmentioning
confidence: 99%
“…[ 5 ] Endovascular internal trapping was recently established as first-line therapy. [ 10 , 12 ] However, some retrospective studies on internal trapping revealed a high incidence of postoperative medullary infarction (30%–47%). [ 1 , 3 ] In our case, we preserved the perforating arteries originating from the VA during surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Angiographic follow-up was conducted with the magnetic resonance imaging angiography or digital subtraction angiography. The aneurysm occlusion status on imaging was assessed with the O'Kelly-Marotta (OKM) grading system ( 17 ), with the aneurysm filling grade of A - complete filling (>95%), B - incomplete (5%-95%), C - neck remnant (<5%), or D - no filling (0%).…”
Section: Methodsmentioning
confidence: 99%
“…A deconstructive approach is to surgically or endovascularly occlude the dissecting segment, but some disadvantages may be involved, including ischemic events in the case of the dominant vertebral artery being occluded, and the need of a bypass in the case of involvement of the posterior inferior cerebellar artery by the dissecting aneurysm ( 12 ). As a reconstructive technique, stent placement and stent-assisted coiling have been applied to treat intracranial vertebral artery dissecting aneurysms, with good outcomes being achieved ( 15 17 ). Flow diverting devices are used to reconstruct the parent artery of the aneurysm and have achieved good prognoses in the treatment of complex anterior circulation aneurysms, but their application in the posterior circulation is still in the exploratory stage.…”
Section: Introductionmentioning
confidence: 99%